2017
DOI: 10.1007/s12160-017-9914-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Linking Adverse Childhood Experiences to Cigarette Smoking Among Young Black Men: a Prospective Analysis of the Role of Sleep Problems and Delayed Reward Discounting

Abstract: Background African American men experience increases in smoking during the young adult transition. Exposure to childhood adversity, a risk factor which disproportionately affects African American men, has been identified as a robust precursor to health risk behavior in general and cigarette smoking in particular. The intermediate mechanisms that transmit the influence of early adversity to smoking behavior are not well understood. Purpose We tested a model of the escalation of smoking behaviors among young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…Our findings that ACEs were associated with greater daytime sleepiness and fatigue, poorer sleep quality, and insomnia symptom severity (in an unadjusted model) are consistent with prior studies demonstrating links of ACEs with self‐reported troubled sleep (Baiden et al., 2015), insomnia symptoms (Chapman et al., 2011; Oshri et al., 2017), global sleep quality (Rojo‐Wissar et al., 2019; Sheehan et al., 2020), and chronic fatigue syndrome risk in adulthood (Heim et al., 2006). Results are also consistent with findings from a recent systematic review, where the aspect of sleep in adulthood most consistently linked to child maltreatment was subjective sleep quality (Brown et al., 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings that ACEs were associated with greater daytime sleepiness and fatigue, poorer sleep quality, and insomnia symptom severity (in an unadjusted model) are consistent with prior studies demonstrating links of ACEs with self‐reported troubled sleep (Baiden et al., 2015), insomnia symptoms (Chapman et al., 2011; Oshri et al., 2017), global sleep quality (Rojo‐Wissar et al., 2019; Sheehan et al., 2020), and chronic fatigue syndrome risk in adulthood (Heim et al., 2006). Results are also consistent with findings from a recent systematic review, where the aspect of sleep in adulthood most consistently linked to child maltreatment was subjective sleep quality (Brown et al., 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Very few studies have included analyses examining associations between ACEs and sleep among Black participants (Boynton‐Jarrett et al., 2021; Gaston et al., 2020; Oshri et al., 2017; Rojo‐Wissar et al., 2021). However, results from those that have done so are generally consistent with our own: that ACEs were associated with reports of poorer sleep quality and more severe insomnia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of the current investigation was on the association between interpersonal discrimination and sleep. However, other factors such as adverse childhood experiences, socioeconomic disadvantage, and exposure to neighborhood adversity may also disproportionately influence the sleep of African Americans relative to other racial ethnic groups (Curtis, Fuller-Rowell, Doan, Zgierska, & Ryff, 2016; Oshri, Kogan, Liu, Sweet, & Mackillop, 2017; Van Dyke, Vaccarino, Quyyumi, & Lewis, 2016). For example, recent research suggests that neighborhood disadvantage accounts for a portion of racial disparities in sleep problems, even after adjusting for individual-level socioeconomic status (Fuller-Rowell, Curtis, El-Sheikh, Chae, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of CM on adolescents is evident across multiple bio-regulatory outcomes ( Mills et al, 2013 ; Oshri, Kogan, Liu, Sweet and Mackillop, 2017 , Oshri, Sutton, Clay-Warner and Miller, 2015 ), including sleep problems ( Xiao et al, 2020 ; Sasser, Oshri, Duprey, Doane and Peltz, 2021 ). Previous research demonstrated that CM severity in adolescence predicted sleep disturbances after one year (e.g., sleep latency, waking episodes, daytime sleepiness; McPhie et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%